Effects of systemic and local cryotherapy on the course of neurodegenerative and autoimmune diseases - A Literature Review - Kalinowska, Weronika; Kulasza, Paulina Sara; Szczepański , Michał; Dzieszko, Natalia; Borowski, Maciej; Szeliga, Aleksandra; Książek , Tomasz Karol; Kozłowska , Kinga; Dembicki, Piotr Mikołaj; Francuziak, Anna Ewelina (Quality in Sport, 2025)
Introduction and Purpose: Cryotherapy, both systemic and local, is increasingly recognized as a complementary method in the treatment of inflammatory, autoimmune, and neurodegenerative diseases. This review aims to summarize current knowledge on the mechanisms of cryotherapy and its impact on clinical outcomes and biomarkers in selected chronic conditions. Description of state of knowledge Cryotherapy exerts anti-inflammatory effects by lowering levels of cytokines such as TNF-α, IL-1β, and IL-6. It also improves microcirculation, modulates hormonal responses and neurotransmission, contributing to pain relief, reduced fatigue, less joint stiffness, and improved quality of life. However, possible side effects include frostbite, dizziness, cold-induced urticaria, and transient hypertension. Contraindications include cardiovascular diseases, cryoglobulinaemia, and cold hypersensitivity. Methods: The literature review included studies from 2000–2025 in databases such as PubMed, Scopus, Web of Science, and Google Scholar. Clinical trials, systematic reviews, and meta-analyses evaluating the efficacy and safety of WBC and LBC were analysed. Conclusions: Cryotherapy is a valuable adjunctive tool for the treatment of diseases with a chronic course and inflammatory components, but its use should be preceded by detailed clinical assessment and patient qualification. Further randomised clinical trials are needed to establish optimal therapeutic protocols and an accurate safety profile.